2015
DOI: 10.1089/thy.2015.0254
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Transcription Factor FOXO1 Is Regulated by Both a Stimulatory Thyrotropin Receptor Antibody and Insulin-Like Growth Factor-1 in Orbital Fibroblasts from Patients with Graves' Ophthalmopathy

Abstract: Background: Activation of thyrotropin receptor (TSHR) and/or insulin-like growth factor (IGF-1) receptor (IGF-1R) enhances HA production and adipogenesis in orbital fibroblasts from patients with Graves' ophthalmopathy (GO) and recapitulates the tissue remodeling characteristic of the orbit in GO. A functional relationship between TSHR and IGF-1R has long been postulated, and recently bidirectional crosstalk between the receptors in GO fibroblasts was demonstrated. Because the transcription factor Forkhead box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…34,35 When FOXO1 is phosphorylated by AKT via the PI3K-AKT cascade, p-FOXO1 is transported from the nucleus to the cytosol, freeing PPARc for activation, while cytosolic FOXO1 is ubiquitinated and degraded. 35,36 In orbital fibroblasts from patients with GO, M22 (a stimulatory TSHR antibody) and IGF-1 increased cytosolic FOXO1 and decreased nuclear FOXO1, indicating that FOXO1 is a downstream mediator of the TSH and IGF1initiated pathogenesis of GO. 36 Moreover, FOXOs act as repressors of hyaluronan production and adipogenesis, as a FOXO enhancer (trifluoperazine hydrochloride) blocks adipogenesis in orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 When FOXO1 is phosphorylated by AKT via the PI3K-AKT cascade, p-FOXO1 is transported from the nucleus to the cytosol, freeing PPARc for activation, while cytosolic FOXO1 is ubiquitinated and degraded. 35,36 In orbital fibroblasts from patients with GO, M22 (a stimulatory TSHR antibody) and IGF-1 increased cytosolic FOXO1 and decreased nuclear FOXO1, indicating that FOXO1 is a downstream mediator of the TSH and IGF1initiated pathogenesis of GO. 36 Moreover, FOXOs act as repressors of hyaluronan production and adipogenesis, as a FOXO enhancer (trifluoperazine hydrochloride) blocks adipogenesis in orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In orbital fibroblasts from patients with GO, M22 (a stimulatory TSHR antibody) and IGF-1 increased cytosolic FOXO1 and decreased nuclear FOXO1, indicating that FOXO1 is a downstream mediator of the TSH and IGF1initiated pathogenesis of GO. 36 Moreover, FOXOs act as repressors of hyaluronan production and adipogenesis, as a FOXO enhancer (trifluoperazine hydrochloride) blocks adipogenesis in orbital fibroblasts. 37 In this report, we showed that indirect inhibition of FOXO1 phosphorylation by idelalisib suppresses the action of PPARc, thereby reducing adipogenic differentiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together these findings suggest a very different mechanism in OAT expansion and underlying orbital fibrosis adipogenesis. Indeed, there is a specific cell-signaling network presenting in fibroblasts from OAT distinct from that in WAT 112 by studies that have highlighted the importance of downstream factors of IGF1-PI3K signalling and revealed that nuclear Forkhead transcriptional factors, FOXOs, serve as convergence points for TSHR and IGF-1R signalling pathways in Graves' orbitopathy 121,122 . Specifically, FOXO1 and FOXO3a served as repressors, which protect orbital fibroblasts from excessive adipogenesis and marked over-production of HA, respectively 121 .…”
Section: [H2] Rituximabmentioning
confidence: 99%
“…Forkhead box transcription factor O1 (FOXO1), encoded by the FOXO1 gene in humans, is a member of the Forkhead transcription factor family, and is widely expressed in living organisms, particularly in the liver, spleen, and lung [6,7]. Forkhead box transcription factor O1 has been identified as an important transcriptional effector in the insulin and insulin-like growth factor 1 (IGF-1) signaling pathways [8,9]. In addition, FOXO1 is involved in numerous cellular functions, such as the cell cycle, apoptosis, and metabolism [10].…”
Section: Introductionmentioning
confidence: 99%